2012
DOI: 10.1097/yic.0b013e328354db12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment discontinuation and hospitalization among nonadherent patients initiating depot or oral typical antipsychotic medications

Abstract: This analysis compared the effectiveness (treatment discontinuation and hospitalization) of depot and oral typical antipsychotics in nonadherent outpatients with schizophrenia. Data from the 3-year, prospective, observational Schizophrenia Outpatient Health Outcome study were used. Time to treatment discontinuation, percentage of patients hospitalized and the mean numbers of hospitalizations were compared for previously nonadherent patients initiating depot typical or oral typical monotherapy. Cox proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In another similar study in Hungary, depot antipsychotics were found to have a lower hospitalization rate than many other oral antipsychotics [19]. Similar findings were observed in the Schizophrenia Outpatients Health Outcomes (SOHO) Study [35], a large pan-European, naturalistic, prospective, observational study of schizophrenia patients. That analysis of SOHO focused on non-adherent patients who were initiated on typical antipsychotics in oral or depot formulations ( n = 431) and found that patients initiated on depot formulations had a significantly lower rate of hospitalization and a lower mean number of hospitalizations following 6 months of treatment.…”
Section: Discussionsupporting
confidence: 59%
“…In another similar study in Hungary, depot antipsychotics were found to have a lower hospitalization rate than many other oral antipsychotics [19]. Similar findings were observed in the Schizophrenia Outpatients Health Outcomes (SOHO) Study [35], a large pan-European, naturalistic, prospective, observational study of schizophrenia patients. That analysis of SOHO focused on non-adherent patients who were initiated on typical antipsychotics in oral or depot formulations ( n = 431) and found that patients initiated on depot formulations had a significantly lower rate of hospitalization and a lower mean number of hospitalizations following 6 months of treatment.…”
Section: Discussionsupporting
confidence: 59%
“…In clinical practice the effectiveness of maintenance antipsychotic medication in reducing the risk of relapse in schizophrenia is often reduced by nonadherence [Novick et al 2012]. A Finnish observational study found that less than half of patients admitted to hospital for the first time with schizophrenia were continuing medication 30 days post discharge [Tiihonen et al 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Depot antipsychotics have been reported to be associated with better adherence to treatment as well as clinical outcomes than oral antipsychotics (Brnabic et al, 2011;Leucht et al, 2011a;Novick et al, 2012). However, it does not always sufficiently prevent relapse especially in the long run.…”
Section: Discussionmentioning
confidence: 99%